Trends and cross-country inequality in the global burden of nutritional deficiencies in children, with projections to 2035: results from the Global Burden of Disease study 2021 - Zhuang, Shihao; Ruan, Meijiang; Chen, Qin; Wang, Qiaomei; Chen, Ting; Wang, Hao; Liu, Shanshan; Chen, Qiudan; Zhang, Chengchen; Hong, Li (Frontiers in Nutrition, 2025)
BackgroundNutritional deficiencies in children are a significant global health concern, contributing to considerable morbidity and mortality. This study evaluates the burden of children's nutritional deficiencies from 1990 to 2021, focusing on key indicators and exploring regional disparities and the role of socio-economic factors.MethodsData from the Global Burden of Disease 2021 study were analyzed for children's nutritional deficiencies across 204 countries and territories. Age-standardized rates (ASRs) for prevalence (ASPR), incidence (ASIR), DALYs (ASDR), and mortality (ASMR) were calculated. Trends were assessed using estimated annual percentage changes (EAPC), and decomposition analysis was conducted to evaluate the drivers of changes in the burden of nutritional deficiencies. Projections to 2035 were made using the Bayesian age-period-cohort model and Health inequality was assessed to analyze transnational health inequality.ResultsFrom 1990 to 2021, the global incidence of children's nutritional deficiencies decreased by 51.51%, with the age-standardized incidence rate (ASIR) dropping to 11,741.75 per 100,000. Global prevalence decreased by 18.44%, and DALYs dropped by 59.57%. Deaths due to nutritional deficiencies reduced by 80.56%. Despite these global improvements, significant regional disparities persisted. Sub-Saharan Africa reported the highest ASIR and ASPR, while high-SDI regions such as North America and Australasia exhibited significantly lower rates. Projections for 2035 indicate continued declines in global incidence, prevalence, DALYs, and mortality, with age-standardized rates expected to decrease annually. By 2035, the ASIR, ASPR, ASDR, and ASMR are projected to reach 7,469.67, 26,386.33, 306.95, and 1.73 per 100,000, respectively. However, disparities in age-standardized rates between high- and low-SDI regions are expected to persist. Health inequality analysis revealed a significant negative correlation between SDI and the burden of nutritional deficiencies, with countries in lower SDI categories facing disproportionately high burdens compared to those with higher SDI.ConclusionsAlthough the global burden of children's nutritional deficiencies is projected to continue declining in both age-standardized rates and total cases, the burden remains disproportionately high in low-SDI regions. These regions face greater challenges in addressing nutritional deficiencies, and targeted interventions aimed at reducing these inequalities are essential. Addressing the significant disparities between low- and high-SDI countries will be crucial for further reducing the global burden of children's nutritional deficiencies.